Cooperative Learning in Islamic Religion and Character Subjects for High School Students - M, Mansur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Learning Islamic religion still requires strengthening in terms of methods. Students are not yet able to apply daily behavior and character that is in accordance with religion and character. Students need methods that can provide benefits from the religious material they have studied at school. This research method uses an experimental method, by comparing the experimental class and the control class. There were 31 students who took part in this research. Data was taken by interviews and tests. The data was processed using data normality and data homogeneity tests. The data is continued with a pair sample test. The research results state that the cooperative learning method can provide an increase in grades of 17 points. Students are given the opportunity to carry out religious activities and practice worship consistently and regularly.